Pelatihan Fotografi dan Konten Produk Pada Siswa Kelas X SMK 1 Semarang Guna Meningkatkan Pemasaran Produk - Desti Fabriana; Agustian Hanan Khanafi; M. Naufal Hawari; Tomi Kurniawan; Kevin Rafael; Ahmad Taufiq Hidayatullah; Ersita Setyowati Putri; Suhariyanto Suhariyanto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Digital marketing is becoming increasingly important in today's digital age. One of the key aspects of digital marketing is engaging visual content, which often involves quality photography. However, a lack of skills in photography and content creation is often a barrier for businesses and marketers. The students are expected to help the process of becoming entrepreneurs who are able to compete in various sectors today as they are trained in entrepreneurship. With the title Visual Strategy of Photography and Content Training for Digital Marketing for Students of SMK N 1 Semarang, this activity was carried out offline with a total of 64 students of SMK N 1 Semarang. Various ways of delivering material, discussion, and training were used during this seminar. The materials were visual photography strategies and marketing content. Evaluation of this activity was carried out with a questionnaire and product photography training, which aims to measure how much the seminar participants understand this training activity. The final result of this community service activity is that the students have a better ability and understanding of photography strategies and digital marketing content.